2019
DOI: 10.1002/adfm.201906996
|View full text |Cite
|
Sign up to set email alerts
|

Pristine Titanium Carbide MXene Films with Environmentally Stable Conductivity and Superior Mechanical Strength

Abstract: 2D titanium carbide (Ti 3 C 2 T x MXene) has potential application in flexible/ transparent conductors because of its metallic conductivity and solution processability. However, solution-processed Ti 3 C 2 T x films suffer from poor hydration stability and mechanical performance that stem from the presence of intercalants, which are unavoidably introduced during the preparation of Ti 3 C 2 T x suspension. A proton acid colloidal processing approach is developed to remove the extrinsic intercalants in Ti 3 C 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
188
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(195 citation statements)
references
References 51 publications
7
188
0
Order By: Relevance
“…Single Ti 3 C 2 T x flake has been demonstrated to have outstanding Young's modulus (≈330 GPa) and tensile strength (≈17.3 GPa), [ 15 ] which suggests that Ti 3 C 2 T x is an excellent building block for fabricating strong films. However, tensile strength values above 120 MPa [ 16 ] and Young's moduli above 10 GPa [ 17 ] have yet to be demonstrated for assembled pure MXene films (Table S1, Supporting Information). To improve the tensile strength of pure MXene films, a wide range of materials, including poly(vinyl alcohol), [ 11,18,19 ] rubber, [ 20 ] cellulose nanofibers, [ 17,21,22 ] bacterial cellulose, [ 23 ] aramid nanofibers, [ 24,25 ] and graphene oxide [ 26 ] have been used in manufacturing of MXene‐based composite films (Table S2, Supporting Information).…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Single Ti 3 C 2 T x flake has been demonstrated to have outstanding Young's modulus (≈330 GPa) and tensile strength (≈17.3 GPa), [ 15 ] which suggests that Ti 3 C 2 T x is an excellent building block for fabricating strong films. However, tensile strength values above 120 MPa [ 16 ] and Young's moduli above 10 GPa [ 17 ] have yet to be demonstrated for assembled pure MXene films (Table S1, Supporting Information). To improve the tensile strength of pure MXene films, a wide range of materials, including poly(vinyl alcohol), [ 11,18,19 ] rubber, [ 20 ] cellulose nanofibers, [ 17,21,22 ] bacterial cellulose, [ 23 ] aramid nanofibers, [ 24,25 ] and graphene oxide [ 26 ] have been used in manufacturing of MXene‐based composite films (Table S2, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…Recently, Chen et al [ 16 ] found that processing of Ti 3 C 2 T x dispersions with ≈0.1 m hydrochloric acid (HCl) solution triggers the self‐assembly of MXene flakes. As a result, Ti 3 C 2 T x films displayed high electrical conductivity (up to 10 400 S cm −1 ) and improved tensile strength from ≈20 to 112 MPa after the HCl treatment.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations